ANALISIS SISTEM KERJA UNIT AVIATION SECURITY (AVSEC) DALAM MENJAMIN KEAMANAN DAN KESELAMATAN PENERBANGAN DI BANDAR UDARA WAMENA PAPUA - Zulfikar Adham; Eny Sri Haryati (Jurnal Publikasi Ekonomi dan Akuntansi, 2023)
Every Airport must have an Aviation Security and safety system to realize the flight is carried out safely and safely in accordance with the flight plan. The research was conducted at wamena Airport, Papua, releated to the security and safety of flights at wamena airport, Papua and Aviation Security support facilities. From the observations of researchers, there are many events that occur at Wamena Airport that can interfere with flight security and safety. This study aims to find out how the Aviation Security unit works in ensuring flight security and safety at Wamena Papua Airport. This study uses a qualitative method with a descriptive qualitative type. This study takes data from documentation, observations and interviews conducted with Senior Aviation Security Officers, Junior Aviation Security and Basic Aviation Security Officers. The data analysis technique used credibility test and data analysis. This research was conducted at Wamena Airport, Papua. The results of the research conducted by researchers that the supporting equipment for the Aviation Security unit at Wamena Airport is adequate but there are equipment that cannot be operated and the lack of human resources for Aviation security officers at Wamena Airport and many do not have a license and SKP.